Incidence of kinesiophobia in patients with osteoarthritis knee an observational cross-sectional study - Rastogi, Aavrati; Kalia, Roop B.; Das , Anindya (International Journal of Research in Orthopaedics, 2023)
Background: The effects of kinesiophobia on pain perception in osteoarthritis patients have remained elusive. The intension of this study is to assess psychometric aspect of pain, functional activity, and kinesophobia in patients with chronic osteoarthritic knee pain. Methods: The study was time bound observational cross-section study, including 50 patients. Kinesiophobia was assessed using Tampa scale of kinesiophobia (TSK-11), while physical function and pain are assessed using WOMAC and VAS scores. Patients were included as per inclusion criteria in the OPD in Department of Orthopedics, AIIMS, Rishikesh, India. Results: It was observed 64% of patients were females while 36% were males. 46% patients had BMI range of 18.5-24.9, while 26% had BMI >=30, 20% had BMI between 25-29.9 and 8% of patients had BMI <18.5. Mean BMI was 25.44±5.70 with minimum BMI of 14 and maximum BMI of 38. It was observed female patients mean WOMAC score was 44.44±19.41, while mean VAS score 4.25±1.05 and mean TSK-11was 33.34±12.57, male patients mean WOMAC score was 35.39±13.62 while mean VAS score was 4.39±0.92, mean TSK-11 was 35.78±14.52. It was observed that there was no substantial difference on basis of gender in all three parameters when compared. This study suggests, there was no significant association between Age and VAS score (p-value 0.017) with Pearson correlation of 0.335. Conclusions: Prospective therapies for kinesiophobia should attempt to reduce pain intensity and functionality improvement.